Insight and the Enlightenment: Why "Einsicht" in Chapter Six of Hegel's Phenomenology? - Reid, Jeffrey (Université d'Ottawa | University of Ottawa, 2016)
Hegel uses the term Einsicht (‘insight’) throughout several key subsections of Chapter Six of the Phenomenology of Spirit (notably in ‘Faith and Pure Insight’ and ‘The Struggle of the Enlightenment with Superstition’). Nowhere else in his work does the term enjoy such a sustained treatment. Commentators generally accept Hegel’s use of the term in the Phenomenology as simply referring to the type of counter-religious reasoning found in the French Enlightenment. I show how Hegel derives the term, through the lens of Kant’s essay, ‘What Does It Mean to Orient Oneself in Thinking?’ from the Pantheismusstreit, the philosophical debate between Mendelssohn and Jacobi about knowledge of God. The Aufklärung provenance of Einsicht shows how a deep complicity between faith and reason, in the form of immediate knowing, leads beyond the Terror to a happier outcome in the Morality section. Finally, passing reference to Einsicht in the Vorbegriff of the Encyclopaedia Logic confirms its role in the ethical and political vocation of Hegel’s Science.
Keywords: Hegel; Insight; Mendelssohn; Kant; Jacobi